Kontribusi Kepemimpinan Pelayan, Status Sosial Ekonomi Keluarga dan Motivasi Berprestasi Terhadap Prestasi Belajar Siswa Di SMK Bali Dewata Denpasar - N.K.B.S.S. Utami; D.G.H. Divayana; I.G.K.A. Sunu (Pascasarjana Universitas Pendidikan Ganesha, 2021)
Learning achievement is a learning outcome that is assessed in the realm of attitudes, knowledge and skills, student achievement is influenced by internal and external factors. This study aims to determine the contribution of servant leadership, family socioeconomic status and achievement motivation to student achievement. To achieve this goal, the researcher used an ex-post facto approach with a research sample of 79 people. The collected data were analyzed using simple regression and multiple regression. Based on the research that has been done, it is found that (1) There is a significant contribution of servant leadership to learning achievement with an effective contribution of 47.89%, (2) There is a significant contribution of family socioeconomic status to learning participation with an effective contribution of 9.59%, ( 3) There is a significant contribution of achievement motivation to learning achievement with an effective contribution of 29.92%, (4) There is a jointly significant contribution of servant leadership, family socioeconomic status and achievement motivation to learning achievement which is 87.40%. Based on the results of this study, it can be concluded that servant leadership, family socioeconomic status and achievement motivation contribute significantly to student achievement, thus these three factors can be used as predictors of student achievement at SMK Bali Dewata Denpasar.